Mobile robot navigation using GPS system - Mohd Rashidi Che Beson (Universiti Malaysia Perlis, 2008)
The aim of this project is to give an overview to investigate into the methods available using current and future technologies of globally navigating a mobile robot using the Global Positioning System (GPS). In this context global positioning refers to the ability to discover ones position when placed in any unknown location on the earth. This system were used GPS-Receiver JP7 as a board to receive data from the satellite. This system also using 8 bit embedded microcontroller 8051 Family which manufactured by Atmel as the main board to control all the application which related to develop Mobile Robot Navigation using GPS System. Mobile Robot is use as a prototype to be control. Mobile Robot has the mission to move from base point to other point using the longitude and latitude given from the GPS Receiver JP7. Mobile robot also using the infrared sensor to evasion any obstacle exist in their path. This system also can be commercialized as the system which can help people in every kind of work because it fully operated automatically.